Analisis Strategi Humas PT. Amplify dalam Mengimplementasikan Program CSR kepada Masyarakat Kota Depok - Astuti, Gadis Kusuma (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2024)
This research aims to analyze the implementation of the Corporate Social Responsibility (CSR) program conducted by PT. Amplify in Depok City. In this context, PT. Amplify focuses on a Corporate Philanthropy program designed to create a positive impact on the surrounding community, particularly vulnerable groups in Sukmajaya District. Through a straightforward yet effective approach, the company strives to understand the environmental conditions and community needs by directly engaging with the local population and observing the challenges they face. This study is expected to provide deeper insights into the role of CSR in enhancing the company's relationship with the community and its impact on overall corporate success. Through this analysis, it is hoped that PT. Amplify can continue to improve its CSR programs and deliver greater benefits to the communities around its operational areas.